Implications Enzymatic Degradation of the Endothelial Glycocalyx on the Microvascular Hemodynamics and the Arteriolar Red Cell Free Layer of the Rat Cremaster Muscle - Yalcin, Ozlem; Jani, Vivek P.; Johnson, Paul C.; Cabrales, Pedro (Frontiers in Physiology, 2018)
The endothelial glycocalyx is a complex network of glycoproteins, proteoglycans, and glycosaminoglycans; it lines the vascular endothelial cells facing the lumen of blood vessels forming the endothelial glycocalyx layer (EGL). This study aims to investigate the microvascular hemodynamics implication of the EGL by quantifying changes in blood flow hydrodynamics post enzymatic degradation of the glycocalyx layer. High-speed intravital microscopy videos of small arteries (around 35 µm) of the rat cremaster muscle were recorded at various time points after enzymatic degradation of the EGL. The thickness of the cell free layer (CFL), blood flow velocity profiles, and volumetric flow rates were quantified. Hydrodynamic effects of the presence of the EGL were observed in the differences between the thickness of CFL in microvessels with an intact EGL and glass tubes of similar diameters. Maximal changes in the thickness of CFL were observed 40 min post enzymatic degradation of the EGL. Analysis of the frequency distribution of the thickness of CFL allows for estimation of the thickness of the endothelial surface layer (ESL), the plasma layer, and the glycocalyx. Peak flow, maximum velocity, and mean velocity were found to statistically increase by 24%, 27%, and 25%, respectively, after enzymatic degradation of the glycocalyx. The change in peak-to-peak maximum velocity and mean velocity were found to statistically increase by 39% and 32%, respectively, after 40 min post enzymatic degradation of the EGL. The bluntness of blood flow velocity profiles was found to be reduced post degradation of the EGL, as the exclusion volume occupied by the EGL increased the effective volume impermeable to RBCs in microvessels. This study presents the effects of the EGL on microvascular hemodynamics. Enzymatic degradation of the EGL resulted in a decrease in the thickness of CFL, an increase in blood velocity, blood flow, and decrease of the bluntness of the blood flow velocity profile in small arterioles. In summary, the EGL functions as both a molecular sieve a lubrication layer for red blood cells (RBCs) motion near the vessel wall, and determines wall shear stress.